Membangun Keterampilan Komunikasi Interpersonal Pada Finalis Putra Putri Kebudayaan Nusantara Provinsi Sumatera Barat - Putra, Gisky Andria; Widuri, Nike (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The Community Service Activities (PKM) are intended to assist the finalists of the Nusantara Cultural Prince and Princess Competition in communicating effectively and building good relationships with others. This will greatly facilitate them in various aspects of life, both in their careers and personal relationships, and help them represent their region excellently and contribute to the advancement of tourism in their respective areas. This activity employs two methods: (1) Discourse and (2) Training, with three stages in its implementation: preparation, execution, and evaluation. The results of the activity show that the implementation of the Community Service activity with the aim of providing understanding and interpersonal communication skills to the finalists of the Cultural Ambassador competition from West Sumatra province has been able to yield positive results for all participants, particularly in terms of their personal development and social relationships. It has built confidence in the participants, strengthened their courage to present ideas or thoughts in front of the public, and indirectly contributed to the efforts to promote and preserve the culture in West Sumatra.